PENGEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) INDUSTRI RUMAH TANGGA (IRT) TEPUNG BUMBU KRISPI DI KELURAHAN KEDUNGKANDANG KOTA MALANG - Ratna Nikin Hardati Ratna Nikin Hardati; Imam Wahyudi Karimulloh; Ade Fitrianti; M. Rifqi Junaidi (Universitas Mataram, 2023)
Abstract : The role of a lecturer is very much needed, especially for the community around the university where the lecturer serves, one of the assistance needed is in terms of economic improvement, this is the background behind the Malang Islamic University to mobilize lecturers in its civitas environment to provide assistance to the community as a form of implementing the Tridharma college is dedication. In the context of this service, the devotees are targeting an UMKM IRT